2010
DOI: 10.1016/j.jvs.2010.01.078
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm shifts in the treatment of abdominal aortic aneurysm: Trends in 721 patients between 1996 and 2008

Abstract: AAA treatment has undergone a profound and sustained paradigm shift, now averaging 84% of repairs performed with EVAR between 2005 and 2008. Overall mortality from AAA repair, including ruptures, was reduced 64% (from 4.9% to 1.8%) during the 13-year study period. Although EVAR and open repair both had improved mortality in the latter half of the series, the primary driver in reduced mortality for AAA repair has been the shift to EVAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…9 Other investigators have noted a modest increase (ϳ20%) in the fraction of complex (juxtarenal, pararenal, and suprarenal) aneurysm anatomy in their current practice. 8, 10 Costin et al noted an increase in the proportion of juxtarenal aneurysms being repaired to 20% in the post stent graft era compared with 6% in the years prior to stent graft availability.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…9 Other investigators have noted a modest increase (ϳ20%) in the fraction of complex (juxtarenal, pararenal, and suprarenal) aneurysm anatomy in their current practice. 8, 10 Costin et al noted an increase in the proportion of juxtarenal aneurysms being repaired to 20% in the post stent graft era compared with 6% in the years prior to stent graft availability.…”
Section: Discussionmentioning
confidence: 97%
“…Recent reports have highlighted this paradigm shift in open aneurysm repair noting that up to 60% of open aneurysm repairs are for juxtarenal aneurysms; some reports detail no deleterious effect of aneurysm complexity on outcomes. 8,9 Other investigators, however, have observed that this anatomic shift in open repair has resulted in increased operative morbidity. 10 Many single center experiences from high volume centers have reported low mortality and moderate morbidity for complex aneurysm repair; however, these reports are limited by cohort size, and inclusion of data spanning decades of experience.…”
mentioning
confidence: 99%
“…1 Compared to open abdominal aortic aneurysm (AAA) repair, EVAR has a short-term survival benefit, as well as other perioperative advantages, such as decreased blood transfusion and shorter-length of hospital stay. 2,3 However, a significant number of patients with infrarenal AAAs continue to undergo open repair.…”
mentioning
confidence: 99%
“…Endovascular abdominal aortic aneurysm repair (EVAR) has almost superseded open surgery for anatomically suitable patients [1]. The Nellix endovascular aneurysm sealing (EVAS) system (Endologix, Santa Rosa, CA) is a novel endograft, which in contrast to conventional EVAR devices comprises two balloon expandable stents, each surrounded by a polymer filled endobag, which conform to the shape of the patients aneurysm thereby providing aneurysm exclusion.…”
Section: Introductionmentioning
confidence: 99%